Imigrantes no carro de Jagrená: a identidade dos sujeito imigrante e a regulação do trabalho engrenadas no discurso da globalização - Andrade, Raquel Resende de (2018)
Migration and globalization are social phenomena intrinsically linked by labor relations. As an economically relevant social phenomenon, the sense of migration is culturally constituted, that is, it is linked to the symbolic-cultural representations of globalized capitalism: concentration and fragmentation of productive chains, division between the circulation of capital and labor, aggregation of the subjects by the technological advance and its disaggregation by the economic and political inequalities. These characteristics of the narrative of globalization result in the paradox of migration: on the one hand, greater ease of human mobility, and on the other, intense selective barriers of entry control imposed by the States. In the scenario of fear and insecurity arising from the volatility of financial capital, competitiveness among states themselves, incapable of meeting the expectations of the welfare state, work represents not only the motor of the desire for better living conditions but the link between the immigrant and the receiving society. In this context, the reflection on the situation of the working immigrant subject in the symbolic representation of globalized capitalism is inserted through the articulation between identity and regulation. The social practice of regulation engenders the discourse of the truth of migration. In order to establish the limits of the circle of protection, the labor force regulation inscribes the immigrant subject in the regime of truth, subjecting him to the position that was strategically destined to him by society and reception, which forms its space of performance. As social practices endowed with sense, identity and regulation, they proceed through the process of demarcating difference in binary opposition: I/other, we/others, inside/outside, national/foreign. In the case of migration, the regime of truth is built around the legal fiction of the nation-state, which holds the control of nationality. In the context of discrimination and vulnerability reserved to immigrant workers, due to the difference of power over nationals, the main challenge to be faced is the persistent denial of their recognition as a subject of rights within the states, both in relations private, as well as institutional. Culturally inscribed in the cradle of social practices. In constant elaboration in the universe of social practices, meaning is always open to new configurations. In the perspective of the encounter with the richness of difference, the greater the fear and insecurity and the deeper the "collateral damages" imposed by the mode of production of globalized capitalism, the greater the importance of the process of individual and institutional reflexivity in the construction of the sense of migration around an anthropoetic, anchored in the triad individual/society/species.